Open architectures of metal carboxylates and mixed metal carboxylates of Cu, Mn, Ca and V: Their syntheses, crystal structures and coordination chemistry - Robles, Julita Climaco (Animo Repository, 2008)
Metal organic frameworks (MOFs) are microporous crystalline substances that exhibit a polymeric networkof M-OCO-M linkages with open pores or cavities their structure. The reaction of a large excess 20% formic acid solution with Cu₂⁺ or in combination with another divalent cation produced a coordination polymer that is connected through a series of formate bridges. The crystal structures of the complexes were characterized by single crystal x-ray diffraction and the results revealed that the formates form an extended network with several layers of the metal formate distributed within the unit cell resulting in an open framework of M-OCO-M rings. The metal formate Cu(HCOO)₂ 4H₂O (Crystal 1) belongs to the monoclinic crystal system with space group P2₁/c and cell dimensions, a = 6.2480(12) Å, b = 8.1320(16) Å, c = 8.1400(16) Å, β= 101.27(3)₀ and V = 405.61(14) Å₃ ; both mixed metal formates crystallize in the monoclinic system with the compound Cu₀.₉₄Mn₁.₀₆(HCOO)₄ 4H₂O (Crystal 2) belonging to the space group P2₁/c with unit cell dimensions of a = 8.8241(18) Å, b =7.1880(14) Å, c = 9.3405(19) Å, β= 97.24(3)₀ and V = 587.7(2) Å₃ and the compound Ca₂Cu(HCOO)₆ (Crystal 3) belonging to the space group, C2/c with the unit cell dimensions of a = 22.3524(45) Å, b = 8.7370(17) Å, c = 6.3200(13) Å, β = 101.462(39)₀ . V = 1209.6(4) Å. Both crystal 1 and Crystal 2 exhibit geometry with respect to the transition metal center and are arranged in a two-dimensional network of metal formate linkages while Crystal 3 forms a multidimensional network of Cu-OCO-Ca linkages with the Cu center forming a hexaformate coordination environment while the Ca metal center is surrounded by seven formate ligands in a distorted pentagonal bipyramidal structure. The complexation of Cu2+ with acetic acid resulted in a dimeric metal carboxylate with a cagelike structure. The four acetate groups that link the two Cu centers form a paddlewheel-like structure with the Cu center exhibiting a square pyramidal geometry. The five-coordinate Cu centers are separated by a distance of 2.6074(5) Å. The metal acetate Cu₂(CH₃COO)₄2H₂O (Crystal 4) crystallizes in a monoclinic space group C2/c with the unit cell dimensions a = 13.1271(22) Å, b = 8.5348(12) Å, c = 13.8117(13) Å β = 117.064(9)o and V = 13780.0(4) Å3. However, CaCu(CH₃COO)₄ 6H₂O (Crystal 5) forms a polymeric network of alternating Ca -OCO- Cu linkages. Unlike the other metal carboxylates, it crystallizes in a tetragonal crystal system with the space group I4/m with the unit cell dimensions a = 11.1163(10) Å, c = (16.1912(72) Å, a = β = y= 90o and V= 2000.8(9) Å3. The structure analysis of Cu[C₆H₄(COO)₂].H₂O reveals that the complex forms a two-dimensional layered framework and belongs to the monoclinic space group C2/c (No. 15) with the unit cell dimensions a = 26.2990(53) Å, b = 6.7080(13) Å, c = 9.8540(20) Å, β = 93.720(30)0 and V= 1734.7(6) Å3. The dimeric K₂V₂(dpot)₂. 7H₂O complex (Crystal 7) contains a diaminopolycarboxylate ligand and exhibits a pentagonal bipyramidal structure around the V center. The complex crystallizes in a monoclinic space group of P2₁/a with the unit cell dimensions of a = 15.573(2) Å, b = 12.601(2) Å, c = 9.234(2) Å; β = 96.98(2)o and V= 1798.6(6) Å3. The V --- V distance of 3.343(2) Å indicates the absence of a V-V bond.